Early structured core training of junior trainees in ophthalmology. Issue 986 (5th December 2007) - Patel, N; Zia, R; Dewitd, D; Morris, S; Ionides, A
Abstract : The implementation of modernising medical careers (MMC) has resulted in some specialties being allocated very inexperienced trainees such as ophthalmology. We aim to describe the process of implementation of MMC and how it may affect the service provision in smaller specialities such as ophthalmology. A methodical approach in a district hospital setting was used to provide early core training to such trainees involving managerial support. The quality of service provided by newer trainees can be enhanced by providing early structured training during induction to create an atmosphere of enthusiasm and continued learning. This example can be used in other units and specialties.